Default Mode Network Aberrant Connectivity Associated with Neurological Soft Signs in Schizophrenia Patients and Unaffected Relatives - Galindo, Liliana; Bergé, Daniel; Murray, Graham K.; Mané, Anna; Bulbena, Antonio; Pérez, Victor; Vilarroya, Oscar (Frontiers in Psychiatry, 2018)
Brain connectivity and neurological soft signs (NSS) are reportedly abnormal in schizophrenia and unaffected relatives, suggesting they might be useful neurobiological markers of the illness. NSS are discrete sensorimotor impairments thought to correspond to deviant brain development. Although NSS support the hypothesis that schizophrenia involves disruption in functional circuits involving several hetero modal association areas, little is known about the relationship between NSS and brain connectivity. We explored functional connectivity abnormalities of the default mode network (DMN) related to NSS in schizophrenia. A cross-sectional study was performed with 27 patients diagnosed with schizophrenia, 23 unaffected realtives who were unrelated to the schizophrenia subjects included in the study, and 35 healthy controls. Subjects underwent magnetic resonance imaging (MRI) scans including a functional resting state acquisition and NSS evaluation. Seed-to-voxel and independent component analyses were used to study brain connectivity. NSS scores were significantly different between groups, ranging from a higher to lower scores for patients, unaffected relatives, and healthy controls, respectively (analysis of variance effect of group F = 56.51, p < 0.001). The connectivity analysis revealed significant hyperconnectivity in the fusiform gyrus, insular and dorsolateral prefrontal cortices, inferior and middle frontal gyri, middle and superior temporal gyri, and posterior cingulate cortex (minimum p-family wise error [FWE] < 0.05 for all clusters) in patients with schizophrenia as compared to in controls. Also, unaffected relatives showed hyperconnectivity in relation to controls in the supramarginal association and dorsal posterior cingulate cortices (p-FWE = 0.001) and in the anterior prefrontal cortex (42 voxels, p-FWE = 0.047). A negative correlation was found between left caudate connectivity and NSS (pFWE = 0.044, cluster size (k) = 110 voxels). These findings support the theory of widespread abnormal connectivity in schizophrenia, reinforcing DMN hyperconnectivity and NSS as neurobiological markers of schizophrenia. The results also indicate the caudate nucleus as the gateway to the motor consequences of abnormal DMN connectivity.